Day Of The Week dan Monday Effect: Fenomena yang Terbuktikan Tidak Konsisten Di Pasar Modal Indonesia - Sumiyana Sumiyana (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This research critiques Sumiyana (2007a) that is actually weak methodological research design. Sumiyana (2007a) investigates trading and nontrading periods return only, or it doesn’t split intra-day return into short interval period. Although Sumiyana (2007a) found strongly the phenomenon of the Monday effect, but it could not capture the inside occurrence in the intra-trading periods. This study examines the day of the week and Monday effect phenomena in the Indonesian Stock Exchange using intraday data in every 30 minutes interval. Samples of the data are the firms listed in LQ45. Sequentially, samples are filtered to stocks that actively traded in the Indonesian Stock Exchange based on trading frequency in observation period from January to December 2006. This study uses regression analysis with multiple dummies constructed by separating trading periods in every day into 12 return periods. This research finds that day of the week phenomena occur consistently in Indonesian Stock Exchange, but the occurrence are not evenly in the same day. In addition, this study concludes that Monday effect exists partially and incidentally only.